ANALYSIS OF DESIGN RULES APPLICATION ON INSTAGRAM FEED RADAR BALI - Rizkita Ayu Mutiarani; Putu Satria Udyana Putra; M. Royan Salsabil; Muhamad Iwan Safri; Wiki Wahyudi (Journal of Aesthetics, Design, and Art Management, 2023)
Purpose: Instagram is one of the social media with a very large number of users, namely 1.3 billion users. The huge number of users is utilized by several media including Radar Bali, a well-known media in Bali using Instagram as a medium for disseminating information and news. Research methods: This research uses observation, visual analysis, and literature study to dissect and find out the design components of Radar Bali's Instagram feed. The research methodology used is descriptive research with a qualitative approach. Findings: The result of the research shows that Radar Bali does not apply design rules properly and consistently. Implications: By not applying design rules to Radar Bali's Instagram feed, the message and information are not maximized.